New modules and assembled systems for the controlled release of drugs in combination / Camillo Benetti - Benetti, Camillo (2016)
Oral administration is the most viable route to deliver drugs and it is also the method which shows the highest patient compliance. Unfortunately some drugs show a low oral bioavalability or they have a short half-life which require taking several doses in one day. The most common oral dosage form is the polymeric matrix, especially swellable matrices. The swellable matrix is a monolithic system of drug dispersed or dissolved a polymeric bed. It can be manufactured using soluble and swellable polymer which can control the release of the drug due to polymer geiification upon in contact with an aqueous medium. The geiification of the polymer takes place gradually on time together with the disentanglement of the polymeric chains which elicit matrix erosion. A drug cannot diffuse through the dry (glassy) polymer, but only via the gelled (rubbery) polymer[4]. Figure 1 shows erosion, swelling and diffusion fronts that are encountered in a matrix.